INFLUENCE OF LIFESTYLE, BRAND IMAGE AND PERCEPTION PRICE INTO PURCHASING DECISIONS BRAND UNIQLO IN SURABAYA CITY - Murtazah, Izah Bana; Purwanto, Sugeng (Yayasan Education and Social Center, 2024)
This research aims to determine the influence of lifestyle, brand image, and price perception on purchasing decisions for the Uniqlo brand in the city of Surabaya. The research method used in this research is quantitative research with the dependent variable being purchasing decisions and the independent variables being lifestyle, brand image and price perception. The number of samples taken was 104 respondents who live in the city of Surabaya who have purchased Uniqlo products at least once using a Likert scale. The sampling technique used in this research was convenience sampling technique with data analysis using Sem-PLS with PLS (Partial Least Square) analysis. From the research results, it was found that lifestyle variables, brand image and price perception had a positive and significant effect on purchasing decisions